Arylation and Alkyne Insertion to C-Acylimines: Rapid Access to 2-Trifluoromethylated and Other Fully Substituted Pyrroles in One Pot - Yaragorla, Srinivasarao; Doma, Arun; Tangellapally, Rajeshwari (Synthesis, 2023)
A one-pot, four-component strategy for the synthesis of trifluoromethylated, and other fully-substituted pyrroles is reported using minimum loading of calcium catalyst at room temperature. A variety of arenes, α-keto aldehydes, amines, and activated alkynes took part in the reaction to produce high-yielding products. Friedel–Crafts arylation and aza-Michael addition are the key reactions in this approach.
Keywords: C-acylimines; trifluoromethyl pyrroles; multicomponent reaction; green chemistry; Friedel–Crafts arylation; calcium catalyst